CD8 T‐cell‐mediated cerebellitis directed against Purkinje cell antigen after ipilimumab for small cell lung cancer. (8th August 2021) - Hardwick, Marc; Nolan, Luke; Nicoll, James A. R.; Jogai, Sanjay; Arriola, Edurne; Joseph‐Pietras, Debora; Norman, Jeanette; Ottensmeier, Christian H. H.; Galea, Ian
Abstract : We report a rapidly progressive and fatal CD8 T‐cell‐mediated cerebellitis after ipilimumab (cytotoxic T‐lymphocyte‐associated protein 4 inhibitor) for small cell lung cancer. Clinical features and histopathology were consistent with an accelerated form of paraneoplastic cerebellar degeneration. A patchy CD8 T‐cell infiltrate spatially corresponded to areas of Purkinje cell loss, with occasional CD8 polarisation towards Purkinje cells. CD20‐positive B cells were sparse. CD8 T‐cell‐mediated cerebellitis after immune checkpoint inhibitor treatment may recapitulate the early stages of paraneoplastic cerebellar degeneration.